AKUNTABILITAS IMPLEMENTASI PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) - Miftahul Janah; Roro Merry Chornelia Wulandari (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Service is one form in improving the welfare of society by the government. The government seeks to provide a good service, although there are still many problems in the field of service. The government seeks to minimize the existing problems by making innovations in service. One of them with the administrative services of the integrated administration of the subdistrict (PATEN). Thus, there is a need for accountability of PATEN implemen-tation. This study uses a qualitative method. Techniques of collecting data using interviews, observation, and documentation. The data obtained in the form of primary data and secondary data. Sampling technique using purposive side. After data is obtained, the data are analyzed through data reduction stage, data presentation, and conclusion. Test the credibility of the data in testing the validity of the data, the researcher uses the technique triangulation method. The result of accountability of the implementation of the integrated administration of the subdistrict (PATEN) in Pakis subdistrict of Malang shows that the PATEN has been organized since January 2017. The scope of services includes the licensing service and the non-licensing field. The implementation of PATEN already meets the existing requirements. Accountability of PATEN implementation is managerial in the form of report of online based accountability to related offices, while to the leadership in the form of accountability report every end of month. Supporting factors are the quality of human resources, infrastructure, and online-based systems. While the inhibiting factor is the internet network is not stable and the lack of human resources (employees). Key word : Accountability, Implementation, PATEN Abstrak: Pelayanan merupakan salah satu bentuk dalam meningkatkan kesejahteraan terhadap masyarakat oleh pemerintah. Pemerintah berupaya memberikan pelaya-nan yang baik, meskipun masih banyak permasalahan di bidang pelayanan. Pemerintah berupaya untuk meminimalisir permasalahan yang ada dengan membuat inovasi dalam pelayanan. Salah satunya dengan adanya pelayanan administrasi administrasi terpadu kecamatan (PATEN). Penelitian ini menggunakan metode kualitatif. Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Data yang diperoleh berupa data primer dan data sekunder. Teknik penentuan sampling menggunakan purposive sampling. Setelah data diperoleh, data dianalisis melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan. Uji kredibilitas data dalam menguji kevalidan data tersebut, maka peneliti menggunakan cara triangulasi teknik. Hasil penelitian akuntabilitas implementasi administrasi terpadu kecamatan (PATEN) di Kecamatan Pakis Kabupaten Malang menunjukkan bahwa penyelanggaraan PATEN sejak bulan Januari 2017. Ruang lingkup pelayanan meliputi pelayanan bidang perizinan dan bidang non perizinan. Implementasi PATEN sudah memenuhi persyaratan yang ada. Akuntabilitas implementasi PATEN secara manajerial berupa laporan pertanggungjawaban berbasis online kepada dinas terkait, sedangkan kepada pimpinan berupa laporan pertanggungjawaban setiap akhir bulan. Faktor pendukungnya adalah kualitas sumber daya manusia, sarana prasarana,dan sistem yang berbasis online. Sedangkan faktor penghambatnya adalah jaringan internet yang tidak stabil dan kurangnya jumlah sumber daya manusia (pegawai). Kata kunci : akuntabilitas, implementasi, PATEN.